Tribochemical degradation of vacuum‐stable lubricants: A comparative study between multialkylated cyclopentane and perfluoropolyether in a vacuum ball‐on‐disc and full‐bearing tests. (27th January 2020) - Kürten, Dominik; Khader, Iyas; Kailer, Andreas
Abstract: In this study, the decomposition of a multialkylated cyclopentane (MAC) and a perfluoro‐poly‐ether (PFPE) lubricant was investigated in a ball‐on‐disc sliding test under vacuum and in a rolling contact fatigue (RCF) test on full bearings. In situ mass spectrometry was conducted to study the tribochemical formation of hydrogen in a steel‐on‐steel ball‐on‐disc sliding contact. Further investigations on lubricant degradation in rolling‐sliding contact indicated fragmentation and oxidation reaction of the MAC oil by interaction with the oxide layer and the nascent bearing steel.Finite element method (FEM) analysis was carried out to model the contact in the ball‐on‐disc experiments and to extract contact surface temperature fields. Post‐RCF hydrogen analysis of bearing components indicated increased hydrogen content in the samples lubricated with the MAC fluid. The RCF tests with PFPE did not indicate any signs of surface damage.